Decreased resting-state neural signal in the left angular gyrus as a potential neuroimaging biomarker of schizophrenia: An amplitude of low-frequency fluctuation and support vector machine analysis - Gao, Yujun; Tong, Xin; Hu, Jianxiu; Huang, Hanjun; Guo, Tian; Wang, Gang; Li, Yi; Wang, Gaohua (Frontiers in Psychiatry, 2022)
Objective: The diagnosis of schizophrenia (SCH) is mainly based on symptomatology, which can easily lead to underdiagnosis and misdiagnosis due to lack of objective biomarkers. This study aimed to explore the value of the amplitude of low-frequency fluctuation (ALFF) based on the support vector machine (SVM) method for the diagnosis of SCH. Methods: 131 SCH patients and 128 age-, gender-matched healthy controls (HCs) underwent a resting-state functional magnetic resonance imaging (rs-fMRI) scans. Imaging data were analyzed with the ALFF and SVM methods. Results: Compared with the HCs, the SCH patients showed decreased ALFF in left angular gyrus (AG), anterior cingulate cortex (ACC), fusiform, right cerebellum, bilateral middle temporal gyrus (MTG), and precuneus (PCu). No significantly increased ALFF was found in any brain regions in SCH patients compared to that in HCs. The SVM results showed that decreased ALFF values of the bilateral PCu could be utilized to separate SCH patients from HCs with an accuracy of 73.36% (190/259), a sensitivity of 91.60% (120/131) and a specificity of 54.69% (70/128). Conclusion: Our results suggest that there is decreased regional activity in SCH patients, and provide a clue that decreased ALFF values of the bilateral PCu could be a candidate biomarker to identify SCH patients from HCs.